Estudio de prefactibilidad para fabricación y comercialización de cabinas para aturdimiento de porcinos (2021)
With this grade project aimed at conducting a pre-invoicability study for the manufacture and marketing of CO2 stun booths, as an alternative to pig pre-encryption at profit plants in Colombia. This study was carried out that has a quantitative and qualitative research methodology in a descriptive way, applying the knowledge acquired during the development of the Industrial Engineering program of the Antonio Nariño University, Bogota, Colombia. Based on the above, a technical questionnaire applied to a customer prospect located in the city of Bogota was designed to validate and explore the possibility of project feasibility, document and have the necessary information to determine that the solution comply the need of the target pig benefit plant market, and that the project is sustainable over time.